Impact of the economic crisis on Greek Millennials' motivations to buy luxury brands and evaluation of premium products purchase frequency - Skiadopoulos, Evagoras (2017)
This research tries to examine and investigate the economic crisis’ impact on the motivations of Greek Millennials to purchase luxury goods as well as the effect of these motivations on premium goods purchase’ frequency. First of all, the researcher attempts to define all the appropriate terms that are useful for the in-depth understanding of the examined topic, as well as, some significant data about the economic crisis are provided. Following this, three main hypotheses were constructed in order to comprehend the matter under investigation thoroughly. These hypotheses can help us gauge the effect of the recession on the impetus for purchasing high-end offerings, as well as determine the possible shift in consumers’ buying frequency regarding premium products, as a result of the economic crisis. At the first stage of our analysis, we tested the existence of relationship between the dependent variable “Frequency of purchasing luxury goods” and the control variables “Gender”; “Age bracket”; “Education level”; and “Employment Status”, in order to examine whether the consumer habits have been affected by these four determinants in conjunction with the recession. The results showed that we have insufficient evidence to support that the 4 aforementioned determinants play a key role in the luxury goods purchase. At the second stage, we tested our primary hypotheses and we have sufficient evidence to reject the null hypotheses 1 and 2 but insufficient evidence to reject the null hypothesis 3. More specifically, it could be said that the economic crisis has a negative effect on luxury goods purchase frequency and there is a positive association between consumer perceptions of luxury brands as “higher quality” and their purchase intentions to increase the frequency of buying such offerings. On the other hand, we have found no evidence to support that peer groups, advertising and packaging design have any type of influence in high-end offerings buying’ frequency. Finally, the limitations of this piece of work are determined and the recommendations for further research are proposed. In particular, it would be useful to examine the matter under investigation by combining the quantitative method with a qualitative one in order to have a more thorough understanding of this topic. Moreover, a bigger sample could give the opportunity for more of a representation of the overall population. This study could also be expanded into different cultures and industrial environments, as well as, future researchers could give more emphasis on luxury services. Last but not least, a longitudinal analysis could give the opportunity to monitor the key similarities or differences amongst different periods of time.